2012
DOI: 10.1519/jsc.0b013e318248ab26
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Responses to Concurrent Strength and Endurance Training with Different Exercise Orders

Abstract: The purpose of this study was to examine the influence of the intrasession sequencing of concurrent strength and aerobic training on the acute testosterone (TT) and cortisol (COR) responses. Ten recreationally strength-trained young men (23.5 ± 0.9 years) performed 2 exercise interventions: aerobic-strength (AS) and strength-aerobic (SA), which consisted of 30 minutes of aerobic exercise on a cycle ergometer at 75% of maximal heart rate and 3 sets of 8 repetitions at 75% of 1 repetition maximum (1RM) in 4 stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
2
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 36 publications
1
34
2
9
Order By: Relevance
“…3RM and 10RM, respectively). Based on both previous literature (Cadore et al 2012) and a pilot study, the endurance loading was conducted on a cycle ergometer (Ergomedic 839E, Monark Exercise AB, Varberg, Sweden) over 30 minutes of steady-state cycling at 65% of subjects' individual maximal aerobic power (Watts), determined during an incremental ergometer test at week 0 and 24, respectively. Subjects were required to keep pedaling frequency constant at 70 rpm but for instances when the subjects failed to keep up the required frequency, intensity was reduced by 15 Watts every minute until the subject could complete the loading.…”
Section: Strength and Endurance Loadingmentioning
confidence: 99%
See 1 more Smart Citation
“…3RM and 10RM, respectively). Based on both previous literature (Cadore et al 2012) and a pilot study, the endurance loading was conducted on a cycle ergometer (Ergomedic 839E, Monark Exercise AB, Varberg, Sweden) over 30 minutes of steady-state cycling at 65% of subjects' individual maximal aerobic power (Watts), determined during an incremental ergometer test at week 0 and 24, respectively. Subjects were required to keep pedaling frequency constant at 70 rpm but for instances when the subjects failed to keep up the required frequency, intensity was reduced by 15 Watts every minute until the subject could complete the loading.…”
Section: Strength and Endurance Loadingmentioning
confidence: 99%
“…Previous studies have emphasized the sensitivity of strength performance to preceding endurance loadings (Leveritt and Abernethy 1999; Lepers et al 2008), leading to reduced force production and possibly compromised long-term adaptations when compared to the 6 reverse loading order (Chtaha et al 2008). Furthermore, it has been shown that force and hormone responses to combined loadings depend on the training status of the subjects and the specificity of the combined protocol performed (Cadore et al 2012;Schumann et al 2013;Taipale and Häkkinen 2013). In physically active men, a recent cross-sectional study showed reduced serum testosterone concentrations during a recovery period of (at least) 2 days when the strength loading was immediately preceded by endurance cycling (Schumann et al 2013).…”
mentioning
confidence: 99%
“…Alguns estudos demonstraram que o TA pode reduzir o ganho de força e potência decorrentes do TF quando ambos os tipos de treino são executados simultaneamente (i.e., treinamento concorrente) e esse efeito têm sido denominado de "efeito de interferência" 17,[26][27][28] . Por outro lado, diversos outros estudos observaram ganhos semelhantes na força muscular comparando o TF com o treino concorrente (TC) 19,20,[29][30][31] .…”
Section: Treinamento Concorrente Em Idososunclassified
“…This phenomenon may occur due to the negative influence of endurance training performance on strength training-induced neuromuscular adaptations (Dolezal and Potteiger 1998;Kraemer et al 1995). Although several studies have focused on concurrent training in young populations García-Pallares and Izquierdo 2011;Izquierdo-Gabarren et al 2010;Cadore et al 2012c;Silva et al 2012), a limited number of studies have explored the effects of concurrent training on strength and endurance performance in older individuals (Izquierdo et al 2004;Cadore et al 2010Cadore et al , 2012aHolviala et al 2010;Sillampää et al 2008;Karavirta et al 2011). Certain studies have recently examined the influence of volume and intensity manipulation and the effects of the intra-session exercise sequence on concurrent training adaptations (Izquierdo et al 2004(Izquierdo et al , 2005Cadore et al 2010Cadore et al , 2011aCadore et al , 2012a.…”
mentioning
confidence: 99%